Dryer Facility Using Hot Air Exhaust from an Air Conditioner (The Philippine Journal of Crop Science, 2013)
One of the major postharvest problems in rice production is drying of harvested material. Storing crop harvests with high moisture content (MC) can result in seed germination, growth of molds, rotting, deterioration or total loss of seed viability, and ultimately, reduction in the market price of grains.drying facilities are usually unavailable, inefficient, or too costly to use because they require fuel or an energy source. Drying of plant samples from a 3-ha experimental field of IRRI can cost more than half a million pesos for one crop season alone using a kerosene-fueled flatbed dryer. The emission from a chiller blower of a centralized air condition (aircon) as a source of hot and dry air for a rice dryer facility was evaluated in this study. Drying ability and characteristics of a dryer chamber using aircon exhaust to dry samples that are to be processed for grain yield data and grain storage and for dry matter yield and/or nutrient analyses were determined. A duct was installed to convey hot air stream from the aircon exhaust to a modified shipping container. The temperature, relative humidity, and drying rates were almost similar at locations near the hot air inlet, at the midpoint, and near the air outlet of the chamber. We conclude that this air conditioner exhaust dyer facility is capable of drying grains to moisture levels acceptable for storage and also facilitates storage of research plant samples for later processing without risk of deterioration or rotting. This dryer facility is also useful for pre-drying samples for dryer matter and chemical analyses. The advantages of this facility are very minimal operating cost, effective drying, elimination of the need for fuel (that would add to operational costs and air pollutants), and safety (i.e., not a fire hazard).